Decreasing prevalence of Trichuris trichiura (whipworm) in the Northern Territory from 2002 to 2012. Issue 5 (17th March 2014) - Crowe, Amy L; Smith, Pam; Ward, Linda; Currie, Bart J; Baird, Rob
Abstract: Objective: To observe the prevalence, disease associations, and temporal trends in Trichuris trichiura (whipworm) infection in the Northern Territory between 2002 and 2012. Design, participants and setting: Retrospective observational analysis of consecutive microbiologically confirmed cases of T. trichiura infection among members of the NT population from whom a faecal sample was obtained for testing by NT Government health care facilities between 1 January 2002 and 31 December 2012. Main outcome measures: Annual prevalence of T. trichiura infection; age, sex, Indigenous status and place of residence of infected patients; percentage of infected patients with anaemia (haemoglobin level, ≤ 110 g/L) and eosinophilia (eosinophil count, ≥ 0.5 × 10 9 /L). Results: 417 episodes of T. trichiura infection were identified over the 11 years from 63 668 faecal samples. The median age of patients was 8 years (interquartile range [IQR], 3–36 years). Patients were predominantly Indigenous (95.3%; P  = 0.001) and from three main geographical areas (Victoria Daly, East Arnhem Land and West Arnhem Land). Infections were associated with anaemia (40.2%) and eosinophilia (51.6%). There was a downward trend in the prevalence of T. trichiura infection diagnosed at NT Government health care facilities, from 123.1 cases (95% CI, 94.8–151.3 cases) per 100 000 Indigenous population in 2002 to 35.8 cases (95% CI, 21.8–49.9 cases) per 100 000 Indigenous population in 2011. Conclusions: T. trichiura is the most frequently identified soil‐transmitted helminth infecting patients in NT Government health care facilities. Cases are identified predominantly in Indigenous patients in remote communities. We have observed a declining prevalence of whipworm infection in the NT.